2000
DOI: 10.1136/gut.47.2.288
|View full text |Cite
|
Sign up to set email alerts
|

Long term outcome after transjugular intrahepatic portosystemic stent-shunt in non-transplant cirrhotics with hepatorenal syndrome: a phase II study

Abstract: Background-Recent small studies on hepatorenal syndrome (HRS) indicate some clinical benefit after transjugular intrahepatic portosystemic stent-shunt (TIPS) but suYcient long term data are lacking. Aim-We studied prospectively feasibility, safety, and long term survival after TIPS in 41 non-transplantable cirrhotics with HRS (phase II study). Patients and methods-HRS was diagnosed using current criteria (severe (type I) HRS, n=21; moderate (type II) HRS, n=20). Thirty one patients (14 type I, 17 type II) rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
232
0
14

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 438 publications
(253 citation statements)
references
References 39 publications
7
232
0
14
Order By: Relevance
“…Inclusion criteria were age between 20 and 80 years, cirrhosis due to alcohol or viral hepatitis, and decompensated liver cirrhosis with indication for TIPS (bleeding in n = 41, refractory ascites in n = 51, or both in n = 18). Exclusion criteria were contraindications for TIPS placement,20, 21 i.e., serum levels of bilirubin >5 mg/dL, spontaneous bacterial peritonitis and manifest hepatic encephalopathy, pulmonary arterial hypertension, and cardiac insufficiency. An invasive control of the TIPS was performed as part of the routine in 74 patients 1‐3 weeks after TIPS insertion 10.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inclusion criteria were age between 20 and 80 years, cirrhosis due to alcohol or viral hepatitis, and decompensated liver cirrhosis with indication for TIPS (bleeding in n = 41, refractory ascites in n = 51, or both in n = 18). Exclusion criteria were contraindications for TIPS placement,20, 21 i.e., serum levels of bilirubin >5 mg/dL, spontaneous bacterial peritonitis and manifest hepatic encephalopathy, pulmonary arterial hypertension, and cardiac insufficiency. An invasive control of the TIPS was performed as part of the routine in 74 patients 1‐3 weeks after TIPS insertion 10.…”
Section: Methodsmentioning
confidence: 99%
“…TIPS (8‐10 mm Wallstent; Boston Scientific) placement was performed as described 20, 21. A single shot of antibiotic prophylaxis of cefuroxime (1.5 g) was administered at TIPS placement.…”
Section: Methodsmentioning
confidence: 99%
“…84 For refractory ascites and progressive HRS, small clinical studies in selected patients have found that transjugular intrahepatic portosystemic shunting may attenuate and/or improve kidney function over several weeks to months. [85][86][87] In a small clinical trial, extracorporeal liver support with the molecular adsorbents recirculation system was shown to improve both kidney function and to extend survival in advanced cirrhosis with established HRS; however, confirmatory data are pending. 88 In progressive HRS, extracorporeal RRT in eligible patients can be used to support loss of kidney function and as a bridge until liver transplantation.…”
Section: Secondary Cardio-renal Syndromes (Type 5 Crs)mentioning
confidence: 99%
“…Indicazioni più rare ed oggetto di studi non controllati condotti su piccoli gruppi di pazienti, alcune delle quali non uniformemente accettate sono: la trombosi portale, la sindrome di Budd-Chiari, l'ascite pleurica [8][9][10], la sindrome epato-polmonare (HPS) [11], la sindrome epato-renale (HRS) [3,[12][13][14][15][16][17], la profilassi del sanguinamento intraoperatorio in pazienti cirrotici con ipertensione portale candidati ad interventi di chirurgia addominale maggiore [8,18,19] e la tutela della pervietà portale pre-trapianto epatico (OLT) [20,21].…”
Section: Da Oltre 20 Anni Lo Shunt Intraepatico Porto-sistemico (Tipsunclassified
“…Less common indications, some of which are not universally accepted, have been investigated by uncontrolled studies conducted on small patient series. These include portal thrombosis, Budd-Chiari syndrome, pleural ascites [8][9][10], hepatopulmonary syndrome (HPS) [11], hepatorenal syndrome (HRS) [3,[12][13][14][15][16][17], prophylaxis of intraoperative bleeding in cirrhotic patients with portal hypertension who are candidates for major abdominal surgery [8,18,19] and maintenance of portal vein patency prior to orthotopic liver transplantation (OLT) [20,21].…”
Section: Introductionmentioning
confidence: 99%